Effect of Regular Exercise and Antioxidant on Superoxide Dismutase (SOD) - Marsal Rispandi; Zulfahri; Novita Sari Harahap (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The components of phenolic compounds contained in antioxidant function antidote to the free radicals that are inevitably generated by physical exertion.Exercise of a moderate level, on a regular basis will increase the sensitivity of endogenous antioxidants so that it can increase the immune system against influenza virus infection. This study aims to prove that regular exercise and antioxidant supplements can prevent oxidative stress which is characterized by increased levels of Superoxide Dismutase (SOD). This study uses an experimental pre and post-test design. Twenty men participated in the study, aged 20-22 years who had a good level of physical fitness, did not smoke, and did not consume supplements and other antioxidants within 2 weeks before and during the study. Participants in the study were randomly assigned to one of two groups, namely group A: regular exercise without antioxidants; group B: regular exercise and antioxidants. Regular exercise is done with a duration of half an hour,the duration of 4 weeks, and the frequency of 3x/week. Before and after treatment, SOD antioxidant levels were measured in both groups. Then the measurement data are tabulated and analyzed. The results showed that there was an increase in SOD levels in the regular exercise and antioxidant groups.